(untitled) (Research, Society and Development, 2023)
The objective of this study was to physicochemically characterize pulp samples of interspecific hybrids between E. oleracea x E. precatoria, as well as to analyze the pulp yield and anthocyanin profile in the samples. The pulp yield for the hybrids studied was 34.63% for hybrid 1 and 24.42% for hybrid 2. Statistically significant differences were found between the two samples for the analysis of lipids, proteins and anthocyanins with the interspecific hybrid 2 presenting the highest levels for the aforementioned analyses. Regarding the anthocyanin profile, it was observed that hybrid 1 had a higher value of cyanidine 3-glucoside compared to rutinoside, contrary to what was observed for hybrid 2, which had a higher content of cyanidin 3-rutinoside. This indicates that between hybrids 1 and 2, there was a genetic predominance of E. oleracea for hybrid 1 and E. precatoria for hybrid 2, in relation to the anthocyanin profile.